Emergy analysis-based study of the sustainable development of Kunming's urban eco-economic system. Issue 2 (3rd April 2023) - Li, Hui; Cao, Lei; Chen, Youbin; Qiu, Huiyi; Huang, Xue; Guo, Wanqi; Wang, Shuntao; Sheng, Weiguo; Zhou, Yilu; Xu, Qing
ABSTRACT: We studied Kunming's urban eco-economic system's evolution from 2009 to 2018, using the emergy theory and method; with the entropy evaluation method, we analyzed the system's natural, social and economic subsystems to know its sustainable development capacity. The results show that the system's emergy structure has clearly improved, and its renewable resources' emergy has been rationally employed. The environment load ratio, after reaching its peak in 2011, has been decreasing, and the environment stress has becoming lower year by year, as is conducive to sustainable development. Its eco-economic system, however, is highly dependent on the internal resources; its emergy self-sufficiency ratio indicates that it does not see sufficient utilization of imported emergy and feels excessive stress on its internal resources. It witnesses relatively high emergy intensity. The current population is about twice of its renewable resources' population carrying capacity, and its dramatically growing population is presenting even high pressure on its social subsystems. This indicates that the living standard per capita in Kunming is lower than the national average. All of these factors will hinder the sustainable development of Kunming's urban eco-economic system. Our analysis of attribute classification shows that it is more appropriate to calculate the tourist revenue by taking into account export emergy. At the same time, the analysis results of sustainable development emergy indexes obtained by ESI, EISD, euehi, euehi' and entropy method are compared, which shows that the entropy method is able to better reflect the dynamic changes of the sustainable development capacity of its urban eco-economic system because it introduces all indicators of social, economic and natural subsystems for evaluation. In a word, sustainable development capacity represents the outcome of tradeoff and coordination of the three subsystems of society, economy and nature, and we can formulate corresponding strategies based on the above research findings.